2019
DOI: 10.1002/jclp.22781
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between trauma‐related psychological distress and physical aggression among urban early adolescents

Abstract: There is convincing evidence that trauma‐related psychological distress and aggressive behavior are highly related among adolescents. The evidence is less clear regarding the direction of this relation. Objective: The purpose of this study was to examine reciprocal longitudinal relations between trauma‐related distress and physical aggression. Method: A predominantly African American sample of early adolescents (N = 2,271; mean age = 12.9) living in an urban, under‐resourced community participated in this inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Second, given the cross‐sectional design of this study, we are not able to determine the direction of effects among the observed relations. Prior studies have found evidence of bidirectional associations among constructs examined in this study (e.g., trauma and physical aggression; Thompson & Farrell, 2019). More research is needed to determine whether adolescents' pattern of involvement in cyber and in‐person aggression and victimization changes over time as a function of their exposure to adversity and trauma.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Second, given the cross‐sectional design of this study, we are not able to determine the direction of effects among the observed relations. Prior studies have found evidence of bidirectional associations among constructs examined in this study (e.g., trauma and physical aggression; Thompson & Farrell, 2019). More research is needed to determine whether adolescents' pattern of involvement in cyber and in‐person aggression and victimization changes over time as a function of their exposure to adversity and trauma.…”
Section: Discussionmentioning
confidence: 54%
“…Positive relations between peer aggression and victimization and exposure to community violence, ACEs, and trauma symptoms have been found among adolescents (Duke et al, 2010; Thompson & Farrell, 2019). However, most studies have used a variable‐centered approach, which does not account for the distinct patterns of peer aggression and victimization supported in the adolescent literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings illustrate the significant impact of expanded forms of adversity and polyvictimization on student development, coping and academic outcomes as evidenced by statements about depression, arguing with teachers, non-attendance and feeling the need to carrying weapons. Expanded forms of adversity, or silent trauma, have received insufficient attention, and the role of trauma or adversity in school discipline has been under examined (Alvarez et al, 2016; Cronholm et al, 2015; Crosby et al, 2018; Kimber & Ferdossifard, 2020; Mallett, 2017; Sanders et al, 2021; Thompson & Farrell, 2019; Turner et al, 2020; Voisin, 2019). The emergent exploratory theory proposes that students who have been suspended or expelled experience multiple and diverse forms of adversity which have influenced coping strategies for this group of students.…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of the impact of adversity, therefore, may not be easily recognizable or fit the expectations of educators. Certain students may not be viewed as traumatized by their experiences, aligning with biased perspectives of these students as perpetrators of adversity rather than experiencing adversity (Thompson & Farrell, 2019; Sanders et al, 2021).…”
Section: Introductionmentioning
confidence: 99%